Strengthening Health Literacy For Improving Theory-Based Decompression Illness Prevention Behavior Health Action Process Approach - Sahmad,; Andi Zulkifli Abdullah,; Muh. Syafar,; Indahwaty Sidin,; Akhmad,; Muhaimin Saranani,; Anwar Mallongi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study explores health literacy in improving decompression sickness prevention behavior among traditional divers of the Bajo tribe in Konawe Regency, Southeast Sulawesi, using the Health Action Process Approach (HAPA) theory. This study aims to understand the level of knowledge of traditional fishermen regarding decompression sickness and how health literacy can play a role in improving prevention behavior. Methods: The method used in this study is the phenomenology method through in-depth interview techniques , and focus group discussions (FGD) on 22 informants which aims to explore informants' knowledge about decompression sickness. The study began in January-July 2024. Data collection using unstructured interview questionnaires. The main themes were arranged to explore the knowledge of traditional fishermen of coastal communities in the Bajo ethnic group about decompression sickness. Results: The results of the study indicate that the knowledge of traditional divers of the Bajo tribe related to decompression sickness is still limited. The themes identified include knowledge of decompression sickness ( Remember , Understanding, Apply), Sources of motivation, enabling factors , pre -action - self-efficacy , Self-efficacy coping . Conclusions:The conclusion of the results of this study is that it is necessary to increase health literacy among traditional divers of the Bajo tribe through the application of HAPA theory to improve decompression sickness prevention behavior, so as to increase the awareness and productivity of diving fishermen.